Systems thinking for general surveillance programs – practical insights and limiting factors to guide resourcing decisions - Kruger, Heleen; Ticehurst, Jenifer L.; Hester, Susan M. (Frontiers in Ecology and Evolution, 2023)
General surveillance programs promise cost-effective ways to contribute to various biosecurity outcomes, including early detection, understanding the spread of invasive species, and evidence of pest and disease freedom to support trade. These programs encourage people from all walks of life to monitor, detect, and report biosecurity threats. Because general surveillance programs make use of the general public and other people already operating in environments where pests may be present, it is often assumed that programs can occur at very low or even no cost. This article discusses lessons learnt about resourcing general surveillance programs from nine in-depth case studies in Australia and New Zealand across a range of biosecurity sectors. Lessons learnt are derived from qualitative analysis using systems thinking, in particular via the concept of limiting factors. It shows that funding is required for program establishment and coordination, adaptive management, and a range of other activities, and there are various sources of transaction cost. It outlines the strategies used to attract and maintain funding and in-kind contributions over time, including how programs navigated various funding challenges. It highlights the importance of using efficient tools and processes for reporting, species identification/disease diagnosis, and data management. The article provides insights that should prove useful for improving return on investment for general surveillance programs.